(untitled) - Sosedova, Jarmila; Slesinger, Jan (Doprava a spoje, 2009)
Cargo during transportation is subject to certain influences, of permanent or temporary nature of the quantitative and qualitative. Theoretical knowledge in the field of physics, chemistry and biology, helping to determine the transport properties of cargo, and then lay down specific procedures for the practical orientation of carriers in order to address issues that cover the entire logistics of transportation.